#### Answer

The distance between the two points is $2\sqrt {37}$.

#### Work Step by Step

The distance between two points is given by the following formula:
$D = \sqrt {(x_2 - x_1)^2 + (y_2 - y_1)^2}$
Let's plug in the same points into this formula to find the distance between them:
$D = \sqrt {(-2 - 0)^2 + (12 - 0)^2}$
Simplify what is inside the parentheses:
$D = \sqrt {(-2)^2 + (12)^2}$
Evaluate the exponents:
$D = \sqrt {4 + 144}$
Add to simplify:
$D = \sqrt {148}$
Rewrite $148$ as the product of a perfect square and another factor:
$D = \sqrt {4 • 37}$
Take the square root to solve for $D$:
$D = 2\sqrt {37}$
The distance between the two points is $2\sqrt {37}$.